The Volodymyrets Village of Rivne Region Residents' Surnames Derived from First Names (Linguostylistic Studies, 2018)
The article analyzes Volodymyrets village of Rivne region residents' surnames derived from first names. The study has revealed that the surnames, originated in the result of the lexical-semantic way of creation, traditionally correlate with the person's first name, mostly Christian by origin, and its colloquial variants. They represent names in their full form (Bohdan, Nazar, Panas, Yarema) or in the form of various folk versions: neutral (Kost’, Kuprii, Panat, Yarosh), diminutive forms of names (Hrytsenia, Danyleiko, Romas’, Tymoshko), and rude- pejorative (Hrytsalo, Vasiuta, Tarakhan). The surnames Kalinka, Gaiko, Dulitsa, Liutko attest to the ancient Slavic names Kalyna, Gaimir or Gaislav, Khristodul, Liutomyr (or any other composite surname based on Lut-). In the analysis of the surnames created by the morphological type of creation, the emphasis is laid on the groups of the anthroponyms characterized by the presence of patronymic and possessive suffixes. They are based mostly on male names (Ivankiv, Ivashyn, Levenko, Levchuk, Omelchak), sometimes female (Maryniak, Odarchuk, Ustych). The word-forming pattern, ending in -uk (-’uk), -chuk is the most productive in the Ukrainian anthroponymy, as evidenced by the analyzed anthroponymic material. The presented and analyzed anthroponimic material confirms the opinion of the researchers that a person's first name is the first and most important source of Ukrainian surnames creation and testifies the importance of further research of regional anthroponymy.
Keywords: anthroponym; surname; personal name; church-Christian name; ancient Slavic name